Solidificação/estabilização do lodo gerado no tratamento de efluente de lavanderia industrial têxtil em blocos cerâmicos acústicos e seu desempenho em câmara reverberante - Castro, Thiago Morais de (2010)
Industrial textile laundries generate considerable amounts of sludge during the treatment of their effluents. As for the appropriate final destination of the sludge, studies have been made concerning its valuation. Other serious common environmental problems are related with the bad acoustic quality in closed places and the noise generated by the traffic of vehicles, mainly in urban areas. The use of absorbing materials of resonant energy and of acoustic barriers has been considered as an alternative for noise control. Several researchers believe that one way of improving the performance of acoustic barriers is to use Helmholtz resonators in their execution. In the case of sludge produced at industrial laundries, the treatment that involves the solidification/stabilization, comes as a viable alternative, as it is capable of keeping polluting elements in a solid source. The aim of this work is to evaluate the viability of incorporating industrial textile laundry sludge, by means of a solidification/stabilization (S/S) process in acoustic ceramic blocks (Helmholtz resonators) evaluating their performance in reverberant camera. Samples of ceramic blocks were produced in reduced scale, a fifth of the real size, using formulations with 5%, 10%, 15%, 20%, 25%, 30% and 35% of sludge in the mass of ceramic clay, to define the maximum appropriate incorporation. In addition, control blocks were produced, manufactured only with ceramic clay. Leaching and solubility, physical mechanical and chemical analyses of the extracts from blocks produced at a maximum incorporation of 25% of sludge were within the established limits by the current norms, however, it was observed that the maximum incorporation of 20% led to a product of higher technical quality. The acoustic ceramic blocks, developed only with clay and with the incorporation of 20% of mixed industrial laundry sludge, were analyzed in reverberant camera in reduced scale, where their resonant absorption coefficients were obtained. It was verified that the values obtained satisfied the project, because the blocks are structures capable of absorbing the sound in specific frequencies, and they were dimensioned to reduce Levels of Resonant Pressure in low frequencies, especially between 125 and 250 Hertz.